PERBANDINGAN PROSES PENYELESAIAN SENGKETA MEALUI MEDIASI DI PENGADILAN DAN DI LUAR PENGADILAN DI INDONESIA - Puspitasari Gustami; Devi Siti Hamzah Marpaung (Jurnal Hukum Lex Generalis, 2024)
This study aims to provide an understanding of the comparison between dispute resolution processes through mediation in court and outside of court in Indonesia, as well as to evaluate the effectiveness of mediation in both settings. The findings indicate differences in the dispute resolution process through mediation in court and outside court, where court mediation tends to be more formal and carries stronger legal authority through a peace agreement decree, while out-of-court mediation is faster and voluntary. Mediation offers advantages in terms of lower costs compared to litigation, shorter resolution time, and the ability to maintain good relationships between the parties involved